2019
DOI: 10.5430/ijhe.v8n1p69
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Interpersonal Emotion Regulation and Interpersonal Competence Controlled for Emotion Dysregulation

Abstract: The aim of this study is to examine the role of interpersonal emotion regulation on interpersonal competency when controlled for emotion dysregulation. The sample of the study consists of 342 (235 female; 107 male) undergraduate students attending to the various departments of a private university in Turkey. The average age of participants was 20.81 (SD=2.29). The Interpersonal Emotion Regulation Scale, Difficulties in Emotion Regulation Scale and Interpersonal Competency Scale were used.  Analyses were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…According to previous studies, health anxiety is a specific manifestation of mental health [39]. Furthermore, studies have shown that interpersonal competence can provide individuals with a sense of security and more emotional support, which is conducive to relieving individual loneliness, improving personal happiness, and improving mental health [40]. Therefore, the following hypotheses are proposed in this study.…”
Section: Hypotheses 221 Interpersonal Competence Emotional Intelligen...mentioning
confidence: 94%
“…According to previous studies, health anxiety is a specific manifestation of mental health [39]. Furthermore, studies have shown that interpersonal competence can provide individuals with a sense of security and more emotional support, which is conducive to relieving individual loneliness, improving personal happiness, and improving mental health [40]. Therefore, the following hypotheses are proposed in this study.…”
Section: Hypotheses 221 Interpersonal Competence Emotional Intelligen...mentioning
confidence: 94%
“…18 Rumination is a maladaptive strategy and a strong predictor for mood, anxiety disorder and depression, and is associated with long working hours and work-related burnout among healthcare professionals. 7,19 The current study found that after the situation, suppression of emotions, and crying (seeking social support) was used as a strategy in disgust and sad emotional state, particularly among the females. A study found that the strategies after the situation were physical distraction and crying, and that suppression during a situation and expression after the experience was the preferred strategy.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, according to the result of this study, interpersonal skill can also appear via virtual interaction; it is the ability possessed by a person in communicating and interacting with other people, including the distance communication, communication carried out in a relationship between two or more people, either verbally or nonverbally, with the aim of achieving common ground. Interpersonal competence developed when students involved in the OCL, that they tried to initiate and sustain social relationships as personality traits (Dumont, 2010;Han & Son, 2020;Malco et al, 2019). Furthermore, it also found that students developed the specific manner of communication skill to interact with others aimed at achieving certain result, such as they tried to find out information from group members, established selfdisclosure, enhanced an assertive, resolved conflicts, provided emotional support, sympathized and respected group members.…”
Section: Discussionmentioning
confidence: 99%
“…Remember, effective interpersonal skills are not just about personality traits, but also about intentional development and practice. (Dumont, 2010;Han & Son, 2020;Malco et al, 2019). Beyond building relationships, interpersonal skills are also about communicating effectively to achieve specific goals within a group.…”
Section: Introductionmentioning
confidence: 99%